Introduction to computer science with C++ - Lambert, Kenneth Alfred, 1951- (Brooks/Cole, 2000)
This book is about: Computer science, computer architecture, and computer languages; Problem-solving fundamentals; More problem-solving fundamentals; Subprograms; ...